Identification and prevention of parasitic crutacean infection on Marine Cultured Fish: a case study in fish hatchery of Universiti Malaysia Sabah - Ruziah Ismail (2014)
The presence of unknown parasite has been detected in marine broodfish tank of fish hatchery, Universiti Malaysia Sabah. This study identified its species and elucidated the effective treatment to eliminate the parasite from culturing system. The unknown parasite was sampled and morphologicallyid entified to the nearest genus and family and Its life stage was recorded. Meanwhile, four different treatments including copper sulfate, treated freshwater, hydrogen peroxide and chlorinated tap water were tested on the parasite in order to identify the most effective treatment to eliminate them. The findings suggested that this unknown parasite was closely resembles to the Gnathia africiana because it has many morphology similarities with those described other author and at least 2 different life stages had been identified including the unfed larvae (zuphea) and fed larvae (praniza). This study also found that chlorinated tap water treatment was able to eliminate parasite from the culturing system with significantly in shorter time (6.95±0.47 min) compared to those observed in treated freshwater (14.43±0.81 min), hydrogen peroxide (18.88±1.08 min) and copper sulfate (49.93±19.51 min) respectively where for recovery process, finding found that in 60 and 1,440 minutes of tap water treatment, there had no recovered parasite after reintroduced with seawater. However, the infested fish can tolerate longer in freshwater (60.00±0.00 min) compared with other treatment The findings from this study were helpful in the disease control management in aquaculture industry particularly on parasitic crustacean related diseases.